INDUKSI DIGITAL MARKETING PADA UKM HEWAN MENCIT DALAM MENINGKATAN PENJUALAN - Triana Triana; Bagas Ardiyantoro; Intan Oktaviani (Jurnal Padamu Negeri, 2025)
The development of digital technology provides great opportunities for Small and Medium Enterprises (SMEs) to improve efficiency and expand their marketing reach. The SME providing laboratory test mice in Surakarta still faces limitations in marketing processes, customer data management, and product distribution, which are mostly carried out manually. This Student Creativity Program (PKM) activity aims to implement digital marketing transformation through the development and application of the Digital Laboratory Test Mice Application of Surakarta as an integrated platform for promotion, ordering, and customer data management. The implementation methods include partner needs analysis, web and mobile-based system design, user training, and effectiveness evaluation. The results show significant improvements in transaction efficiency, ease of product information access, and market reach expansion for the SME. Through the application’s implementation, the partner SME is able to adapt to digital trends, strengthen competitiveness, and enhance service professionalism in providing laboratory test mice.